2011
DOI: 10.1002/anie.201101905
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Cyclopropenation Reaction of 1‐Alkynes with α‐Alkyl‐α‐Diazoesters Catalyzed by Dirhodium(II) Carboxylates

Abstract: As a result of enormous ring strain, cyclopropene compounds display a range of diverse reactivities in both noncatalytic and transition-metal-catalyzed transformations, thus presenting unique opportunities for organic synthesis. [1,2] To further enhance the synthetic potential of cyclopropenes, the development of expeditious methods for the synthesis of enantioenriched cyclopropenes is highly desirable.[3] In this context, a cyclopropenation reaction of alkynes with diazo compounds that is catalyzed by chiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(67 citation statements)
references
References 71 publications
2
65
0
Order By: Relevance
“…They reported that [Rh 2 (S-topttl) 4 ], a new dirhodium(II) carboxylate complex that incorporates Ntetrabromophthaloyl-(S)-tert-leucinate as chiral bridging ligands, catalyzes the cyclopropanation reaction of terminal alkynes with 2,4-dimethyl-3-pentyl--alkyl--diazoacetates to give 1,2-disubstituted 2-cyclo-propenecarboxylates in good to high yields and with up to 99% ee [144] (Scheme 8).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that [Rh 2 (S-topttl) 4 ], a new dirhodium(II) carboxylate complex that incorporates Ntetrabromophthaloyl-(S)-tert-leucinate as chiral bridging ligands, catalyzes the cyclopropanation reaction of terminal alkynes with 2,4-dimethyl-3-pentyl--alkyl--diazoacetates to give 1,2-disubstituted 2-cyclo-propenecarboxylates in good to high yields and with up to 99% ee [144] (Scheme 8).…”
Section: Applicationsmentioning
confidence: 99%
“…Hashimoto and coworkers [50], in 2008 disclosed the first example for the enantioselective amination for an allylic C-H bond of silyl enol ethers 212 derived from cyclic ketones 211 or enones of six-membered-rings by using [(2-nitrophenylsulfonyl)imino]phenyliodinane (213; NsN=IPh) as a nitrogen precursor catalyzed by dirhodium (II) tetrakis[N-tetrachlorophthaloyl-(S)-tert-leucinate] complex 33e [144,145], [Rh 2 (S-TCPTTL) 4 ] which has provided, after desilylation, N-pNs-protected (S)--aminocyclohexanone 215 as a sole product in up to 72% ee (Fig. 32).…”
Section: Applicationsmentioning
confidence: 99%
“…In 1993, Hashimoto, Ikegami and co-workers first reported their famous complex, Rh 2 (S-PTTL) 4 [76,77], as a catalyst that manifested (along with its variants) high enantioselectivity levels in wide range of organic transformations [2,54,[78][79][80][81][82][83][84]. For example, in enantioselective [2,3]-sigmatropic rearrangement of the cyclic propargylic oxonium ylide shown in Scheme 5a, Rh 2 (S-PTTL) 4 provided the best enantioselectivity of 79% ee of the corresponding allenic bearing benzofuran-3-one product (Scheme 5a) [85].…”
Section: Global Catalyst Symmetrymentioning
confidence: 99%
“…9 Consequently, we were surprised when treatment of methyl siloxyvinyldiazoacetate ( 3-Me ) with 4-nitrocinnamaldehyde at room temperature, catalyzed by dirhodium carboxylates, gave epoxide 4a with trans -divinyl substutuents in excellent yield (Scheme 3). Use of chiral catalysts that included Hashimoto’s Rh 2 ( S -PTPA) 4 10 and Davies’ Rh 2 ( S -DOSP) 4 11 did not give evidence of enantiocontrol in this transformation, and dirhodium carboxamidates exhibited very low reactivity towards dinitrogen extrusion of 3 . Surprisingly, use of Cu(CH 3 CN) 4 PF 6 , which is even more reactive towards dinitrogen extrusion from diazo compounds than is rhodium acetate, 12 gave the Mukaiyama-aldol addition product 5 in high yield when the reaction performed at 0°C without effecting diazo decomposition (Scheme 3).…”
mentioning
confidence: 93%